An Interpretation of the Data from "The Effect of Mesh Size on the Fishing Efficiency of Sardine Gill Nets" - Dutt, S (Fishery Technology, 1965)
An Interpretation of the Data from "The Effect of Mesh Size on the Fishing Efficiency of Sardine Gill Nets"